2020
DOI: 10.1111/1467-8500.12420
|View full text |Cite
|
Sign up to set email alerts
|

Legislating deliberative engagement: Is local government in Victoria willing and able?

Abstract: Growing dissatisfaction with representative democracy and concomitantly, the increasing expectation that citizens assert more influence over public policy have seen the emergence of more participatory and deliberative forms of governance in public management practice. This article explores the attempt of the state government of Victoria, Australia to legislate for mandatory deliberative engagement as part of its local government strategic planning instruments. The ambition of the reform was significant; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However 'advocacy', as a key component of deliberative systems, is notable by its absence in the updated Acteven though many matters of great importance to local communities are decided at higher levels of government. Instead, the new Act focuses on the inputs of deliberative activities rather than the outputs, even though research suggests the decision-making context is more influential than the engagement process for determining the success of community participation (Savini and Grant 2020). This study supports that supposition by highlighting the important role advocacy by local governments can play in influencing the policy making environment, in partnership with deliberative and traditional community engagement practices.…”
Section: Discussionmentioning
confidence: 50%
“…However 'advocacy', as a key component of deliberative systems, is notable by its absence in the updated Acteven though many matters of great importance to local communities are decided at higher levels of government. Instead, the new Act focuses on the inputs of deliberative activities rather than the outputs, even though research suggests the decision-making context is more influential than the engagement process for determining the success of community participation (Savini and Grant 2020). This study supports that supposition by highlighting the important role advocacy by local governments can play in influencing the policy making environment, in partnership with deliberative and traditional community engagement practices.…”
Section: Discussionmentioning
confidence: 50%
“…Perhaps a high point for the requirement of these types of processes was witnessed in 2020, with the Government of Victoria introducing compulsory 'deliberative engagement' at the local government level-a requirement that is by no means unproblematic for particular types of councils in that jurisdiction, many of whom indicated that they thought it was an ill-founded idea in their submissions to the process (Savini and Grant 2020). Nevertheless, the overall point is that these types of processes are now embedded and have led to the commercialisation, if not professionalisation, of community engagement (see Christensen and Grant 2020).…”
Section: Requirements For Community Engagement In Planning Processesmentioning
confidence: 99%
“…Place‐based policymaking can be understood as part of a broader trend away from centralised principal/agent forms of public administration towards a more decentralised and horizontal governance frameworks (Carey et al., 2015; Levi‐Faur & Klijn, 2012; Marsh et al., 2017; Shergold, 2013). In recent years, these trends have seen an increasing emphasis on service user consultation and codesign, and a flourishing industry of community engagement consultants (Bice et al., 2019; Savini & Grant, 2020).…”
Section: Introductionmentioning
confidence: 99%